Penerapan Teknik Budidaya Serta Hubungan Antara Pemangkasan Dan Peningkatan Kesuburan Tanah Terhadap Peningkatan Produktivitas Kakao Di Kabupaten Pidie - Akhmad Baihaqi; A. Humam Hamid; Ashabul Anhar; Yusya Abubakar; T. Anwar; Yuvi Zazunar (Jurnal Agrisep, 2015)
ABSTRACT. Improvement of production and quality of cocoa can be done through the implementation of appropriate technology adoption and implementation of good cultivation techniques in the field of cocoa farmers. Implementation of pruning, composting, composting with different treatment doses will produce a diverse production. This study aimed to analyze the implementation of the adoption of cultivation techniques performed by cocoa farmers in Pidie district. The research location in District Mila and Padang Tijie, with samples of cocoa farmers and land farmers. The samples were conducted by purposive sampling with descriptive analysis model to examine the application of technology and cultivation techniques. Randomized block design was used to examine the use of compost and trimming of various treatments.The results showed that the application of integrated technologies in cocoa cultivation but not perfectly executed. The absence of treatment replications resulted in farmers forget. Cocoa with a dose of compost 9 kg / plant, has the effect of the dry weight of the cocoa beans tend to be greater in the treatment done trimming. A combination of composting 13.5 kg / plant by pruning showed the highest average at the variable total weight of dried fruit and cocoa beans. Organic fertilizers 15 tons/ha yield the best cocoa.